A Study of Conventional and Digital Drawing: A Comparative Analysis of Traditional and Digital Drawing Techniques (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Drawing is one of the major forms of expression within the visual arts. The history of drawing is as old as the history of humankind. Early man drew pictures before they learned how to write. They used to communicate with the drawings. We are living in an era where the evolution and use of technology in our daily life has become ubiquitous throughout the world. Drawing style and drawing material has also gradually changed with the passage of time. Today’s artist are witnessing the creation and evolution of the internet, computers, Pen Tablet, software and the countless other technological devices. Whether it is an artist or designer, they are moving away from traditional drawing material. Today, artists are using graphic tablets which allow them to achieve the same results on their computers with less time. This paper explores the study of the evolution of conventional drawing and digital drawings. A detail study in this context shows the overview of difference between the digital drawing techniques from the conventional drawing art.